Understanding the value of a PhD for post‐doctoral registered UK nurses: A survey. (28th March 2022) - Hampshaw, Susan; Cooke, Jo; Robertson, Steve; Wood, Emily; King, Rachel; Tod, Angela
Abstract: Aims: This study investigated, 'What is the perceived value of a PhD to doctoral and postdoctoral nurses in the UK?' Background: Little is known about what happens to the careers of nurses who undertake a doctorate and whether they use these skills in the next career steps. Methods: Nurses ( n = 47) with doctorates were recruited via professional networks and twitter (@NMAHP_DoctorateStudy). Qualitative responses from the nurses were analysed using thematic analysis. Results: Three themes emerged from qualitative analysis: impact on career, utilization and value, and impact on self. Conclusions: This study provides one of the few insights into how doctoral trained nurses understand and experience the value and utility of their studies to themselves and others. Implications for nurse management: Nurse managers can play a crucial role in generating a research‐led culture within their clinical setting. This would include promoting an understanding of research as something directly related to patient benefit rather than an abstract, intellectual activity.